2020
DOI: 10.3389/fphar.2020.00971
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 6 as a Therapeutic Target in B cell-associated Hematological Malignancies

Abstract: B lymphocytes play a critical role in humoral immunity. Abnormal B cell development and function cause a variety of hematological malignancies such as myeloma, B cell lymphoma, and leukemia. Histone deacetylase 6 (HDAC6) inhibitors alone or in combination with other drugs have shown efficacy in several hematological malignancies, including those resistant to targeted therapies. Mechanistically, HDAC6 inhibitors promote malignant tumor cell apoptosis by inhibiting protein degradation, reinvigorating anti-tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 79 publications
(113 reference statements)
2
11
0
Order By: Relevance
“…36 OGT can directly stabilize ASXL1 through O-acetylglucosamine modification, thereby inhibiting bone marrow cell differentiation and H3K4 methylation. 37,38 Then, reactivation of OGT will induce bone marrow cell differentiation and inhibit leukemia. 39 Asthana and other researchers have found that the use of OGT inhibitors and OGT gene knockdown inhibits GlcNAcylation, leading to the differentiation and apoptosis of leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 OGT can directly stabilize ASXL1 through O-acetylglucosamine modification, thereby inhibiting bone marrow cell differentiation and H3K4 methylation. 37,38 Then, reactivation of OGT will induce bone marrow cell differentiation and inhibit leukemia. 39 Asthana and other researchers have found that the use of OGT inhibitors and OGT gene knockdown inhibits GlcNAcylation, leading to the differentiation and apoptosis of leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…OGT expression is upregulated in pre‐B acute lymphocytic leukemia (pre‐B‐ALL), which inhibits the proliferation of Nalm‐6 cells and slows the rate of apoptosis after OGT, indicating that OGT is closely related to the pathogenesis of pre‐B‐ALL 36 . OGT can directly stabilize ASXL1 through O‐acetylglucosamine modification, thereby inhibiting bone marrow cell differentiation and H3K4 methylation 37,38 . Then, reactivation of OGT will induce bone marrow cell differentiation and inhibit leukemia 39 .…”
Section: Discussionmentioning
confidence: 99%
“…In MYC -induced lymphoma, HDAC6 has a different function than HDAC1 [ 67 ]. Indeed, HDAC6 is unique with two catalytic domains, a mainly cytoplasmic location, and substrates such as tubulin and heat-shock proteins [ 68 ]. Current research on HDAC6 is fueled by specific inhibitors like rocilinostat, which induces an unfolded protein response (UPR) in DLBCL cells concomitant with overloading of the proteasome [ 69 ].…”
Section: The Pharmacological Targeting Of Histone Acetylationmentioning
confidence: 99%
“…Diffuse large B-cell lymphoma (DLBCL) is the most common category of non-Hodgkin lymphoma (NHL), accounting for approximately 30% of NHL cases worldwide. [1][2][3] DLBCL is more prevalent in elderly patients and tumor mass growing one or more lymph nodes and extranodal sites. 2,4,5 The high incidence rate and heterogeneity of DLBCL have attracted extensive attention.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] DLBCL is more prevalent in elderly patients and tumor mass growing one or more lymph nodes and extranodal sites. 2,4,5 The high incidence rate and heterogeneity of DLBCL have attracted extensive attention. [6][7][8] Hence, it is important to reveal the underlying molecular mechanism of the origins and development of DLBCL for medical diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%